Understanding Religious Moderation and Quranic Verses on Interfaith Relations Among Ulama in North Sumatera Binjai City - Al Fiqri Ardiansyah; Hasnah Nasution; Ali Darta (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2024)
Wasathiyyah in Islam is a concept of moderation that emphasizes justice, balance and tolerance, as reflected in the Qur’an and hadith. However, these values are often misunderstood and misused. This article highlights the role of the Ulama of Binjai City in instilling Islamic moderation values in society. The focus of this research is the view of the Ulama of Binjai City on the relationship between Islam and other religions, according to the teachings of the Qur’an and the interpretation of the Indonesian Ulema Council (MUI) of Binjai City. This research uses the Living Qur’an method, which combines textual analysis with real-life contexts to understand the views and attitudes of the ulama towards followers of other religions. The results show that the Qur’an teaches the importance of justice and tolerance in interfaith relations, which the Binjai City Ulema interpret as an obligation to respect the beliefs of others while maintaining their own. These clerics gained their understanding of moderation from their teachers and primary sources. The findings indicate that the internalization of Islamic moderation values by the Ulama of Binjai City contributes to interfaith harmony in society